Clinicopathological profile of spectrum of thrombocytopenic cases – a cross sectional study - Dr. Mourouguessine Vimal; H. Shaheena Parveen (Tropical Journal of Pathology and Microbiology, 1970)
Background: Thrombocytopenia is a common finding in many hospitalized patients and its etiology is diverse.Aim: This study aimed to do a detailed clinicopathological correlation of various cases of thrombocytopenia in adults by elucidating the various etiological factors, severity of thrombocytopenia, various mode of clinical presentation and the proportion of patients presenting with bleeding manifestations.Materials and Methods: This is a cross sectional study done for a period of 2 months. The relevant clinical and investigatory findings all patients with a platelet count of less than 1,50,000 were collected from the patients’ medical records.Results: A total of 120 patients were included out of which 71 (59.2%) males and 49 (40.8%) females and most of the study population belonged to 20-60 age group. The platelet count was <50,000 - 24(20%), 50,000 – 1,00,000 – 65 (54.2%), 1,00,000 to 1,50,000 - 31(25.8%). The etiological diagnosis of patients were Dengue - 26 (21.67%), Malaria – 8(6.7%), Enteric fever – 7 (5.9%), Septicemia – 6(5%), Chronic liver disease – 20 (16.7%), Chronic kidney disease – 4 (3.4%), Diabetes – 9 (7.7%), Malignancy – 2 (1.67%), Coronary artery disease – 4 (3.4%), Pregnancy – 6 (5%) Hematological disorders – 22 (18.4%) and miscellaneous – 6 (5%). 54 (45%) presented with fever and 16 (13.3%) with bleeding manifestations.Conclusion: Infectious diseases was the most common cause of thrombocytopenia. Chronic liver disease was the commonest non infectious cause followed by diabetes. Most presented with fever followed by bleeding manifestations. Early recognition and continuous monitoring of patients with thrombocytopenia can avoid bleeding manifestations including fatal intra cranial haemorrhage.